1985
DOI: 10.1029/tc004i007p00613
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic evolution of the Meatiq infrastructure, Central Eastern Desert, Egypt

Abstract: The Pan‐African basement exposed in the Meatiq area, Central Eastern Desert, Egypt, was found to possess tectonic styles belonging to infrastructure, transition and super‐structure levels. Tectonic style of the infrastructure was developed during an old orogeny in the Lower Pan‐African, and overprinted by those of the transition and superstructure levels of a younger orogeny in the Middle and Upper Pan‐African, respectively. In the Lower Pan‐African, old sequences of sediments and volcanics, together with ophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Habib et al (1985a) identified and described several thrust sheets structurally above the Um Báanib Orthogneiss, including the Abu Fannani Thrust Sheet. In the description and discussion which follows we have adopted the Abu Fananni Thrust Complex, as a term for all the five thrust sheets (Fiadiya-, Gabal-Meatiq-, Abu Zohleiga-, Um Esh Hamra-and Abu Fannani thrust sheets).…”
Section: Geology Of the Meatiq Gneiss Dome And Surrounding Areamentioning
confidence: 98%
“…Habib et al (1985a) identified and described several thrust sheets structurally above the Um Báanib Orthogneiss, including the Abu Fannani Thrust Sheet. In the description and discussion which follows we have adopted the Abu Fananni Thrust Complex, as a term for all the five thrust sheets (Fiadiya-, Gabal-Meatiq-, Abu Zohleiga-, Um Esh Hamra-and Abu Fannani thrust sheets).…”
Section: Geology Of the Meatiq Gneiss Dome And Surrounding Areamentioning
confidence: 98%
“…The studied rock units have pre Pan-African and Pan-African age by many authors (e.g. El Gaby, 1983;Asran, 199;Khudeir et al, 1995;Kamal El-Din, 1993;Ragab et al, 1993 andHabib et al, 1985). Recent studies suggest the Neoproterozoic age for the investigated rocks (e.g.…”
Section: Introductionmentioning
confidence: 71%
“…This assemblage occurs essentially as tectonically dismembered sheets, blocks, and fragments embedded in a metasedimentary succession. Host rocks of the FIC were extensively investigated by numerous authors (e.g., Akaad & Shazly, 1975; Andresen, El‐Rus, Myhre, Boghdady, & Corfu, 2009; Fritz et al, 2014; Habib, Ahmed, & El Nady, 1985; Loizenbauer et al, 2001; Neubauer, 1962; Neumayr, Hoinkes, Puhl, Mogessie, & Khudeir, 1998). Thus, in‐depth geochronological, metamorphic, structural, and tectonic studies on rock units hosting the TTG suite of the FIC (the Fawakhir and Meatiq rocks) have been carried out.…”
Section: Geological Settingmentioning
confidence: 99%
“…Thus, in‐depth geochronological, metamorphic, structural, and tectonic studies on rock units hosting the TTG suite of the FIC (the Fawakhir and Meatiq rocks) have been carried out. These studies showed that the Fawakhir ophiolitic mélange (736.5 Ma; Andresen et al, 2009) occurring within the eugeoclinal thrust sheet formed in a fore‐arc setting, whereas the Meatiq dome (630.8 Ma; Andresen et al, 2009) is a younger structural feature interpreted to have formed as a result of NE‐SW tectonic shortening occurred during an oblique collision of East and West Gondwana (e.g., Akaad & Shazly, 1975; Andresen et al, 2009, 2010; Habib et al, 1985; Loizenbauer et al, 2001; Neumayr et al, 1998; Schuermann, 1966). The Meatiq dome is made‐up of high‐grade granitic orthogneiss occurring at the structurally lowest part that is overlain by a dominant metasedimentary succession consisting of quartz‐rich schists intercalated with metapelitic schists.…”
Section: Geological Settingmentioning
confidence: 99%